Development of E-Student Worksheet Based Task-Based Learning Through LiveWorksheets.com for High School Students - Puan Maharani; Marhamah Ahmad Hamid (STAI Hubbulwathan Duri, 2024)
The objective of this study is to determine the development of electronic student worksheet using LiveWorksheets interactive website that is reliable, useful, and efficient on the material produced. This kind of research and development (RD) tries to create an e-student worksheet product. Liveworksheet task-based learning development is accomplished using the ADDIE design development, which includes analysis, design, development, implementation, and evaluation. Students in Class 11-TKJ at SMK Perbankan Riau in 2023 served as the study's test subjects. A validation sheet was used to assess the reliability of the e-student worksheet, a response questionnaire was used to determine how useful the e-student worksheet was, and learning outcomes tests were used to determine the efficiency of the e-student worksheet. The results of material expert validation and learning expert validation amounted to 91.8% with very good criteria and 82.6% with very good criteria. Comparison of results before and after using e-student worksheet is pre-test 76.8 and post-test 85.88. Therefore, it is known that there is an increase in student understanding by using e-student worksheet through LiveWoksheets. The questionnaire response of students received an average rating of 78.2% with good criteria. While the teacher's questionnaire response obtained a score of 80% with good criteria. Thus, it can be concluded that interactive e-student worksheet through LiveWorksheets is reliable, usable, and efficient also can increase student learning motivation.